QUALITY OF LIFE IN CHILDREN WITH CRONIC KIDNEY DISEASE UNDERGOING RENAL REPLACEMENT THERAPY; REVIEW - Iga Dewi (JURNAL KEPERAWATAN CIKINI, 2021)
Introduction: Chronic Kidney Disease (CKD) in children will have an impact on the quality of life in chidren, to be able to continue the growth and development of children with ESRD, renal replacement therapy, dialysis, end renal transplant, is needed. Purpose: To identify in the literature studie that evaluate the quality of life in children with CKD undergoing renal replacement therapy end validated instruments in Pediatrics. Method: review of the literature with searches conducted in the following database: Medline, Pubmed, Proques, CINAHL and Cochrane Library databases were searched from 2010 to 2020 in quality of life in children with CKD undergoing renal replacement therapy. Studies were included following criteria (1) quality of life in children with CKD (2) Instruments QOL in children (3) study were included renal replacement therapy: peritoneal dyalisis, hemodialisis, and renal tranplantik. (4) the full-text article was available in English. Results: eight studies were included in this review. Included that evaluated the quality of life of children with CKD undergoing renal replacement therapi by means of evaluation instruments of quality of life. Conclusion: Quality of Life in Children with various QOL instruments from eight articles concluded that QOL is better in children who have undergone kidney transplantation, compared to children with PD and HD. QOL of children with PD was better than children with HD in all domains